Cutaneous manifestations of dermatomyositis characterized by myositis-specific autoantibodies [version 1; peer review: 3 approved] - Naoko Okiyama; Manabu Fujimoto (F1000Research, 2019)
Dermatomyositis (DM) is an inflammatory myopathy with characteristic skin manifestations, the pathologies of which are considered autoimmune diseases. DM is a heterogeneous disorder with various phenotypes, including myositis, dermatitis, and interstitial lung disease (ILD). Recently identified myositis-specific autoantibodies have been associated with distinct clinical features. For example, anti-melanoma differentiation-associated protein 5 antibodies have a high specificity for clinically amyopathic DM presenting rapidly progressive ILD. Furthermore, anti-transcriptional intermediary factor 1γ antibodies found in patients with juvenile and adult DM are closely correlated with malignancies, especially in elderly patients. Finally, patients with anti-aminoacyl-transfer RNA synthetase antibodies share characteristic clinical symptoms, including myositis, ILD, arthritis/arthralgia, Raynaud’s phenomenon, and fever; thus, the term “anti-synthetase syndrome” is also used. With a focus on the characteristic cutaneous manifestations in each subgroup classified according to myositis-specific autoantibodies, we introduce the findings of previous reports, including our recent analysis indicating that skin eruptions can be histopathologically classified into myositis-specific autoantibody-associated subgroups and used to determine the systemic pathologies of the different types of antibody-associated DM.